Sekolah Judicial Review: Strengthening the Legal Culture of Civil Society Organizations in the Indonesian Legal System - Tanto Lailam; Irfan Nur Rachman; Rahmat Muhajir Nugroho; Mukhtar Zuhdy; Rofi Aulia Rahman (Universitas Negeri Semarang, 2026)
The research-based legal empowerment program, entitled